Pengolahan Data Indeks Kepuasan Masyarakat (Ikm) Pada Balai Besar Pengembangan Budidaya Air Tawar (Bbpbat) Sukabumi Dengan Metode Weight Average Index (Wai) - Yanti Nurkhalifah, Iwan Rizal Setiawan , (PROCEEDING IC-ITECHS 2014, 2014)
Community satisfaction index use as a benchmark to assess the level of quality ofservice in the form of a questionnaire which must be done collectively, unified, focused, and consistent  as  a  reference  to  determine  the  level  of  performance  of  the  service  unit  of government agencies in order to achieve the expected quality. in the use of data processing application  CSI  is  still  use  evenly,  one  of  them  in  the  center  freshwater  aquaculture development ( CFAD ) Sukabumi, the application is still not use, the data of the respondents and the data is still conventional CSI. so that by the time the data were collected may appear many errors such as data loss, tucked, or a mistake when entering values. so that the resulting information about agency services to the community are not appropriate. to produce an appropriate and accurate information is required CSI questionnaire data processing application, which use in the data collection phase of the respondents and the CSI data is easily and accurately. the questionnaire data processing can perform processing CSI although the data is still not reached the maximum number specified. the amount of data that has been processed will be displayed on the information in the form of percentage and value of the level of quality of service agencies.